NIKAH TANPA WALI DALAM PERSPEKTIF FIKIH MUNAKAHAH - Abd. Shomad, Moh. Ali (IAIN Tulungagung, 2015)
Marriage is an agreement on the benefits of the genitals with the terms andcertain pillars. Pillars of marriage among others, husband, wife, guardian,shighat namely consent and qabul, and two witnesses. The terms of aguardian: Islam, men of legal age, independent, fair, intelligent, in a stateihtiyar, not in a state of Ihram or mahjur. Father, grandfather, brother bladder, his half-brother, son brother bladder, boyâs brother had the same father, biological uncle (brother of the biological father), Uncle had the same father (his half-brother of the father), son of the uncle, al-Maula. Hakim. Marriage without the legal guardian of the scholars agree not valid, except Hanafiyah.Kata kunci: Pernikahan Tanpa Wali, Fikih Munakahah